Inactivation of Fgf3 and Fgf4 within the Fgf3/Fgf4/Fgf15 gene cluster reveals their redundant requirement for mouse inner ear induction and embryonic survival. Issue 5 (12th November 2021) - Zelarayan, Laura; Vendrell, Victor; Domínguez‐Frutos, Elena; López‐Hernández, Iris; Schimmang‐Alonso, Kiril; Alonso, María Teresa; Alvarez, Yolanda; Maier, Hannes; Anderson, Matthew J.; Lewandoski, Mark; Schimmang, Thomas
Abstract: Background: Fibroblast growth factors (Fgfs) are required for survival and organ formation during embryogenesis. Fgfs often execute their functions redundantly. Previous analysis of Fgf3 mutants revealed effects on inner ear formation and embryonic survival with incomplete penetrance. Results: Here, we show that presence of a neomycin resistance gene ( neo ) replacing the Fgf3 coding region leads to reduced survival during embryogenesis and an increased penetrance of inner ear defects. Fgf3 neo/neo mutants showed reduced expression of Fgf4, which is positioned in close proximity to the Fgf3 locus in the mouse genome. Conditional inactivation of Fgf4 during inner ear development on a Fgf3 null background using Fgf3/4 cis mice revealed a redundant requirement between these Fgfs during otic placode induction. In contrast, inactivation of Fgf3 and Fgf4 in the pharyngeal region where both Fgfs are also co‐expressed using a Foxg1 ‐Cre driver did not affect development of the pharyngeal arches. However, these mutants showed reduced perinatal survival. Conclusions: These results highlight the importance of Fgf signaling during development. In particular, different members of the Fgf family act redundantly to guarantee inner ear formation and embryonic survival. Key Findings: Presence of a neo gene in the Fgf3 locus affects embryonic survival and penetrance of inner ear defects. Fgf3 and Fgf4 are redundantly required for inner ear induction. Presence of selection markers in the Fgf3 locus affect Fgf4 expression.